Esophagectomy without thoracotomy in the treatment of neoplasm of the esophagus.: our experiences - Piacenza, Guillermo; Bergalli, Luis; Carriquiry, Luis; Piñeyro, Alberto; Rodríguez, José Luis (Cirugía del Uruguay, 1987)
In view of 21 cases of carcinoma of the esophagus tratad with esophagectomy without thoracotomy, some aspects of surgical technique, complications an('.I results are analyzed. The importance of indication relatad with stage and topography of the lesion is pointed out. Adva.ntage an disavantages of this techinque are cons. idere, d wit out orgetting that this is a palliative procedur-ec o ,ge ,11 ,good antidysphagic result is the aim ol this proc.ed 1-e.